2019
DOI: 10.1136/jramc-2019-001198
|View full text |Cite
|
Sign up to set email alerts
|

Concept of error and nature of nursing error detectors in military hospitals: a qualitative content analysis

Abstract: Background and objectivesNursing errors can cause irreparable consequences. Understanding the concept of error and the nature of nursing error detectors can significantly reduce this type of errors. The present study was conducted to explain the concept of error and the nature of nursing error detectors in military hospitals.Materials and methodsThe present study was conducted on eight nurses working in different wards of military hospitals using a qualitative approach to content analysis proposed by Graneheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…A non-accommodating environment, which emphasises professional autonomy, collegiality and self-regulation, is unlikely to foster incident reporting (Malik et al, 2010). Consistent with earlier literature (Ajri-Khameslou et al, 2018; Lynch et al, 2017; Vrbnjak et al, 2016), the current study also showed that the considerable time and effort required in the reporting process influenced healthcare professionals’ willingness to report. In a Swedish study, healthcare professionals indicated that incident reports implied extensive paperwork (Carlfjord et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…A non-accommodating environment, which emphasises professional autonomy, collegiality and self-regulation, is unlikely to foster incident reporting (Malik et al, 2010). Consistent with earlier literature (Ajri-Khameslou et al, 2018; Lynch et al, 2017; Vrbnjak et al, 2016), the current study also showed that the considerable time and effort required in the reporting process influenced healthcare professionals’ willingness to report. In a Swedish study, healthcare professionals indicated that incident reports implied extensive paperwork (Carlfjord et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…In another study conducted in Iran (2018), patients rated their information about this aspect as low. 17 In addition, lack of awareness of patients from complaints-handling authorities is a barrier to the detection of medical errors 28 and makes them vulnerable and caused moral distress, and decreases moral sensitivity in health care providers. 29…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in Iran (2018), patients rated their information about this aspect as low. 17 In addition, lack of awareness of patients from complaints-handling authorities is a barrier to the detection of medical errors 28 and makes them vulnerable and caused moral distress, and decreases moral sensitivity in health care providers. 29 As can be seen, in the present study, patients considered this area as the least important among all aspects of patient rights which can be a threat to the practice of patients' rights.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined health care errors in clinical settings (Ajri‐khameslou, Aliyari, Pishgooie, Jafari‐Golestan, & Farokhnezhad Afshar, 2019; Balas, Scott, & Rogers, 2004; Barkhordari‐Sharifabad & Mirjalili, 2019; Meurier, 2000) including the ICU (Donchin et al, 2003; Khammarni et al, 2015; Venkategowda, Rao, Mutkule, & Taggu, 2014). Different strategies, approaches, recommendations and principles for error prevention are also cited (IOM, 2000; WHO, 2007; Zikhani, 2016).…”
Section: Introductionmentioning
confidence: 99%